On saturation phenomenon in energy harvesting based on nonlinear piezoelectric materials coupled to a portal frame foundation with ideal and non-ideal excitations - Rocha, Rodrigo Tumolin [UNESP] (2016)
Recently, the interest and research about energy harvesting has been increasing substantially in the technical-scientific community. With the great world demand for electrical energy, many researchers, in Brazil and in the World, have concentrated their efforts to seek new energy sources. In addition, with the technological advances is possible to use low-power consumption devices, that are, most of time, powered by a battery, which are limited energy sources having the necessity of recharging or substituting them periodically. In the energy harvesting process, the electrical energy is obtained through the conversion of mechanical energy created by a vibrating source in the environment using a transducer. Among the most common energy transduction mean, the use of piezoelectric materials has been of great interest in the energy harvesting matter due to its ease of application and its use to harvest energy in a wide range of frequencies. Vibration sources in the environment may occur in structures by vehicle traffics, a train movement, sea waves and even people. With that, the objective of this work is to study the energy harvesting using a nonlinear two-degrees-of-freedom portal frame platform with a nonlinear piezoelectric material coupled to one of its columns and externally base-excited. The nonlinear platform possesses two-to-one internal resonance between its two vibration modes. The nonlinearities of the piezoelectric material is considered as a nonlinear mathematical relation. Moreover, this work is separated in two parts to the analysis of the external excitations. In the first part, a harmonic force base-exciting the system is considered. In the second part is considered an electro-dynamical shaker with harmonic output. The employed methodology to carry out the analysis of this work was: the application of the method of multiple scales to find the best configuration of the parameters, and to find some kind of phenomena due to the two-to-one internal resonance; in the following were carried out several numerical simulations using the method of Runge-Kutta of 4th and 5th order with variable step seeking to optimize the energy harvesting through parametrical variations, bifurcation diagrams, FFTs, time histories and other typos of simulations. In general, it will be done two much important comparisons: the influence of the nonlinearity of the piezoelectric material and the use of the harmonic force and the shaker to the energy harvesting. The results showed great influence of the nonlinearity of the material, and using the electro-dynamical device it was possible to have a considerably gain in the system stability.